Genetic and molecular evidence that brown trout Salmo trutta belonging to the Danubian lineage are a single biological species. Issue 5 (28th October 2018) - Kalayci, Gokhan; Ozturk, Rafet C.; Capkin, Erol; Altinok, Ilhan
Abstract : We tested for reproductive isolation between Salmo trutta abanticus, S.t. labrax, S.t. caspius and S.t. fario by conducting crosses to produce F1 and F2 offspring. We also estimated the extent of genetic divergence between all three entities by examining sequence variation across the coI, d‐loop and cytb mitochondrial genes. All of the F1 cross‐types were successfully produced. After 2 years of culturing, F2 generation were produced as well. Fertilization, hatching and survival rates and hatching performance of F1 and F2 generations were evaluated. F2 generation had similar performance to their parent. Fertilization, hatching, larval survival rate and hatchery performance of F1 and F2 generation were similar except pure bred F2 S.t. abanticus . Purebred F1 individuals shared similar coloration patterns and spots with their parents but direction of the hybridization appeared to be decisive on morphology of hybrids. Some of the hybrids exhibit different morphological characters than their parents. Based on partial alignments of the three genes, phylogenetic analysis showed that these S. trutta are gathering within the same clade and appeared as monophyletic group. We found that there were some morphologic and genetic variation among S. trutta subspecies but the degree of variation does not warrant species level recognition. These findings indicate that the four subspecies constitute a single biological entity, corresponding to different morphs of the Danubian lineage. We therefore recommend that S. trutta belonging to Danubian lineage in Turkey be referred to as Salmo trutta and that strains be named according to location, such as Abant, Caspian, Black Sea and Anatolian.